2022
DOI: 10.3389/fneur.2022.873925
|View full text |Cite
|
Sign up to set email alerts
|

The Indirect Impact of COVID-19 on Major Clinical Outcomes of People With Parkinson's Disease or Parkinsonism: A Cohort Study

Abstract: BackgroundThe indirect impact of the COVID-19 epidemic on major clinical outcomes of people with Parkinson's disease (PD) or other parkinsonism is unknown.ObjectivesThe study aimed to (1) describe changes in healthcare services during the first epidemic bout in people with PD or parkinsonism; (2) compare the occurrence of hospitalization for any PD-related major clinical outcomes in 2020 with 2019; (3) investigate the factors, including changes in healthcare services, associated with major clinical outcomes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…These indirect effects of COVID-19 are more confirmed and may be more common and more harmful than the direct effects of viral infections 1,9,10 . The worsening of motor and non-motor symptoms has been attributed to stress, physical inactivity, pharmacodynamic effects, dramatic changes in routine, and social isolation 11,12 . The impact of stress on PD progression has been previously investigated and proven to negatively affect the course of the disease 1,2,4 .…”
Section: Discussionmentioning
confidence: 99%
“…These indirect effects of COVID-19 are more confirmed and may be more common and more harmful than the direct effects of viral infections 1,9,10 . The worsening of motor and non-motor symptoms has been attributed to stress, physical inactivity, pharmacodynamic effects, dramatic changes in routine, and social isolation 11,12 . The impact of stress on PD progression has been previously investigated and proven to negatively affect the course of the disease 1,2,4 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth mentioning that recent studies have shown that NSCs can fight against COVID-19 [ 26 ]. The susceptibility of the elderly to COVID-19 infection, and the high mortality rate, are strongly associated with indirect clinical outcomes in PD patients [ 102 ]. Therefore, compared with the other above-mentioned compounds, NCS has more advantages in the protective potential of anti-PD.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies showed that essential health services for chronic noncommunicable diseases were reduced or disrupted during the COVID-19 pandemic, potentially leading to a worse outcome or higher risk of death [11,12]. The comparison shows a dramatic increase in emergency admissions.…”
Section: Reports Of Neurological Manifestations Of Omicron Infectionmentioning
confidence: 99%